Economic Burden in Direct Cost of Chronic Obstructive Pulmonary Disease at a Tertiary Care Teaching Hospital: A Prospective Observational Cohort Study - Patel, Kruti D.; Lalwani, Tarachand; Shah, Kartik (Indian Journal of Pharmacy Practice)
Background: Chronic Obstructive Pulmonary Disease (COPD) is a disease of significantly increasing in terms of economic burden due to its increasing prevalence and high costs. In India because of growing pressure on the health care budget, appropriate reasoning of current expenditure and future investments in public health care becoming a priority. Objective: To evaluate Burden of cost in patients of Chronic Obstructive Pulmonary disease. Material and Method: A prospective, observational, non-interventional, cohort study was carried out over a period of six months for Chronic Obstructive Pulmonary Disease (COPD) inpatients at medical wards of Sheth V. S. hospital, Ahmedabad, Gujarat, India. Burden of cost had been evaluated as a part of Pharmacoeconomic. Direct medical and non-medical cost were included in the burden of cost. From the drug rate manual of hospital, cost for drugs and investigation were calculated. Result: Total numbers of 70 patients in which 53 were male and 17 were female with mean age of 60.21 ± 10.29. Minimum total direct medical cost was Rs. 864.00 and maximum was Rs. 5876.00 with a mean ± SD 2418.12 ± 839.73, in which medicine cost was high. Minimum total direct non-medical cost was Rs. 149.00 and maximum was Rs. 1069.00 with a mean ± SD 528.10 ± 212.72, in which additional charges was high. Minimum total direct cost was Rs. 1103.00 and maximum was Rs. 6945.00 with a mean ± SD 2946.22 ± 1009.23. Direct medical cost contribute 82% and direct non-medical costs contribute 18% of total direct cost. Conclusion: COPD has a substantial impact on health-care costs particularly for hospitalization. Pharmacoeconomic evaluation of COPD is essential to obtain optimal therapy at lowest price and alternative treatment plans to gain appropriate health care services Costs of COPD were exceptionally low in India compared to data obtained from developed countries.
Keywords: Chronic Obstructive Pulmonary Disease; direct medical cost; Pharmacoeconomic